INOVASI PEMBUATAN KULIT MOONCAKE DARI TEPUNG KACANG MERAH - Dina mayasari soewoyo (Journal FAME: Journal Food and Beverage, Product and Services, Accomodation Industry, Entertainment Services, 2022)
The purpose of this study was to determine the ideal formulation in making Mooncake skin made from local food, namely red bean flour and to determine the public's acceptance of these innovative products. The research method used is descriptive quantitative research, with data collection techniques, namely distributing questionnaires to expert panelists and consumer panelists, experimentation, documentation and literature study. The data analysis technique was carried out by means of a preference test or organoleptic test on the taste, color, aroma and texture of the product. The data from the questionnaire results were processed using descriptive statistics by looking for the Score, Mean, Median, Mode and Standard Deviation. The product experiment was carried out with 3 formulas, namely making Mooncake with skin made from original wheat flour, a mixture of wheat flour and red bean flour, and 100% red bean flour. To obtain research results, questionnaires were distributed to expert panelists and consumer panelists by providing product samples. The conclusion of this study is that from 2 formulations of Mooncake product innovations that use ingredients from red bean flour for the skin, judging from the mean, median, mode, and standard deviation values from the organoleptic test questionnaire, it was found that expert panelists and consumer panelists preferred innovation of Mooncake products whose skin is made from 100% red bean flour, both in terms of taste, aroma, color and texture dimensions.